2014
DOI: 10.1589/jpts.26.1891
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Antioxidants and Exercise on Muscle Atrophy Induced by Ischemic Reperfusion

Abstract: [Purpose] This study aimed to determine whether muscle atrophy induced by ischemic reperfusion injury in rats can be prevented by the administration of antioxidants and exercise. [Subjects] Rats were randomly divided into five groups: non-treated, ischemic, exercise, ascorbic acid and exercise, and tocopherol and exercise. [Methods] The relative weight ratio of the soleus muscle and the length of the soleus muscle fiber cross-section minor axis were used for the evaluation of muscle atrophy. Pain was assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…One of the main mechanisms of osteoarthritis pathogenesis is oxidative stress promoted by enhanced free radical production and therefore, not surprisingly, increased MDA levels are observed in the serum of the patients suffering from this condition [ 12 , 13 ]. Many studies have shown that high-intensity exercise increases oxidative stress and intensifies lipid peroxidation processes [ 41 43 ], which is mainly the result of muscle damage and fatigue induced by exercise [ 43 ] However, the effect of physical activity on lipid peroxidation intensity is not completely known as it may be affected by many variables such as exercise type, intensity and duration [ 44 , 45 ]. According to Dixon et al [ 46 ], it is the intensity of resistance exercise bout that plays the main role in oxidative stress generation [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the main mechanisms of osteoarthritis pathogenesis is oxidative stress promoted by enhanced free radical production and therefore, not surprisingly, increased MDA levels are observed in the serum of the patients suffering from this condition [ 12 , 13 ]. Many studies have shown that high-intensity exercise increases oxidative stress and intensifies lipid peroxidation processes [ 41 43 ], which is mainly the result of muscle damage and fatigue induced by exercise [ 43 ] However, the effect of physical activity on lipid peroxidation intensity is not completely known as it may be affected by many variables such as exercise type, intensity and duration [ 44 , 45 ]. According to Dixon et al [ 46 ], it is the intensity of resistance exercise bout that plays the main role in oxidative stress generation [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The degree of oxidation is determined by exercise type, intensity, and duration 23 , 24 ) . Lipid peroxidation generated by active oxygen and ROS is caused by the oxidation of polyunsaturated fatty acid, which is the main ingredient of biological membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, stronger resistance to tourniquet-induced oxidative stress and inflammatory response may be assumed to suppress knee swelling, knee pain, and quadriceps muscle loss, resulting in lower QW and walking disability immediately after TKA. IPC and EPC have been [17][18][19][20]. Hence, this study focused on a form of exercise called LST that confers both hypoxic and exercise stimulation to working skeletal muscle and subsequently investigated whether preoperative LST program would suppress knee and thigh swelling and knee pain, resulting in decreased QW and walking disability immediately after TKA.…”
Section: Discussionmentioning
confidence: 99%
“…These factors can be attributed to surgical trauma and tourniquet-induced ischemia-reperfusion (IR) injury [12][13][14], which generates vigorous oxidative stress and inflammatory responses characterized by the toxic reactive oxygen species formation, inflammatory cell recruitment, and endothelial barrier failure, resulting in impaired organ function [15]. Additionally, ischemic and exercise preconditioning (IPC and EPC) have shown to prevent IR injury and are well-known interventions for inhibiting IR injury-induced tissue damage in various organs, including skeletal muscle [16][17][18][19]. Therefore, tourniquetinduced early QW can be prevented by IPC and EPC.…”
Section: Introductionmentioning
confidence: 99%